The Political Economy of Higher Education Finance: How Information and Design Affect Public Preferences for Tuition - Philipp Lergetporer; Ludger Woessmann (Institute of Labor Economics (IZA), 2019)
Public preferences for charging tuition are important for determining higher education finance. To test whether public support for tuition depends on information and design, we devise several survey experiments in representative samples of the German electorate (N>19,500). The electorate is divided, with a slight plurality opposing tuition. Providing information on the university earnings premium raises support for tuition by 7 percentage points, turning the plurality in favor. The opposition-reducing effect persists two weeks after treatment. Information on fiscal costs and unequal access does not affect public preferences. Designing tuition as deferred income-contingent payments raises support by 16 percentage points, creating a strong majority favoring tuition. The same effect emerges when framed as loan payments. Support decreases with higher tuition levels and increases when targeted at non-EU students.
Keywords: I22; H52; D72; D83; 330; tuition; higher education; political economy; survey experiments; information; earnings premium; income-contingent loans; voting